Теоретичні та технологічні основи обмінних процесів при інжекційній десульфурації чавуну різними реагентами - Шевченко, А.П.; Manachin, I.A.; Двоскін, Б.В.; Кисляков, В.Г.; Шевченко, С.А.; Єлісєєв, В.І.; Вергун, О.С.; Остапенко, О.В. (Physico-technological Institute of Metals and Alloys, 2023)
The results of calculation and analytical developments for the implementation of the most rational mechanism of various technologies of desulfurization of hot metal based on the injection of lime and magnesium are presented. It is shown, that the ways of implementing rational decisions and the mechanism of these processes are different. When blowing calcium oxide, it is necessary to organize a chemical interaction with the participation of Al introduced from outside, as well as the destruction and dispersion of the zone of flow from the lance into hot metal using gasforming additives in cast iron. A comparison of the calculated costs of various reducing agents indicates that the use of magnesium and hot metal manganese seems to be the least rational, since it is accompanied by the highest costs. For all particle sizes, a velocity of less than 80 m/s is irrational, since it is accompanied by a sharp decrease in the depth of particle penetration into the molten iron. It is shown, that when blowing powdered reagents with a particle diameter of < 0.8 mm, particles practically do not penetrate into the molten iron. This phenomenon is undesirable, as it is accompanied by a sharp decrease in the active surface of the introduced reagent. In the case of mono-injection of magnesium, it is necessary to ensure a granular composition of the reagent and a high (more than 50 m/s) flow rate into the molten iron. When granular reagents with particle diameters of more than 0.4 mm are blown in, the velocity parameter is decisive, since it provides the possibility of introducing reagent particles into the hot metal to a depth of up to 20–25 mm. In accordance with the recommended parameters for the injection of granular magnesium in most hot metal treatments, the magnesium content in cast iron after refining exceeds the equilibrium values of the equilibrium system [Mg] – [S]. The latter provides stability and reliability of the process of hot metal desulfurization by mono-injection of granular magnesium. The degree of desulfurization is up to 95–99 %. Theoretical provisions are confirmed experimentally.